Asian religions aren't that exotic - TSE, Justin K. H. (Institutional Knowledge at Singapore Management University, 2012)
Toronto filmmaker Quentin Lee's The People I've Slept With (2009) may seem like a sex-comedy at odds with Asian Canadian religious values. The story is set in California - but the movie is classed as Canadian because of Lee's Torontonian roots - and revolves around the love lives of Angela Yang and her gay best friend Gabriel.